The sub-standard ship and port state control in South Africa - Clark, Grant (Institute of Marine and Environmental Law, 2024)
In our modern era we often find we are spectators to the development occurring around us. This is particularly true of trade and industry. As the net of trade and industry has slowly been cast across the globe, so it has made demands on all who subscribe to its lordship. More effective means of productivity, lower costs, higher turnover and more efficient transport. Demands which we race to meet, all of which are important but none more important than the need for transport. Without a satisfactory transport system industry would die. There would be no accessible markets except those where the product was made, and those markets would soon be saturated. The importance of an effective and efficient transport system has not gone unnoticed, and the result is that this system, which was initially birthed to facilitate and serve trade and industry, has itself graduated to that status. Inevitably with this graduation it has adopted the principles and vision of its mentor. Money is sovereign in the world of industry and trade, indeed a cruel and ruthless sovereign.